Impact of private sector credit on economic growth in Nigeria - Emmanuel O. Olowofeso; Abiola O. Adeleke; Anthony O. Udoji (CBN Journal of Applied Statistics, 2015)
Motivated by the need to avoid possible parameter bias associated with previous works, we examined the impacts of private sector credit on economic growth in Nigeria using the Gregory and Hansen (1996) cointegration test that accounted for structural breaks and endogeneity problems. The method was applied to quarterly data spanning 2000:Q1 to 2014:Q4, while the fully modified ordinary least squares procedure was employed to estimate the model coefficients. We found a cointegrating relationship between output and its selected determinants, albeit, with a structural break in 2012Q1. Amongst others, findings from the error correction model confirmed a positive and statistically significant effect of private sector credit on output, while increased prime lending rate was inhibiting growth. In view of the financial intermediation roles of deposit money banks, the paper supports the ongoing efforts of the Central Bank of Nigeria (CBN) in promoting a sound and realsector-friendly financial system. Also, the commitment of the CBN to the gradual reduction in interest rates is meaningful for the country's growth objectives.
Keywords: C01; C32; E44; G17; G21; O16; 330; Private sector credit; Economic growth; Cointegration; Structural break